(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Described herein is a method for fuel monitoring in a fuel tank of an automobile, the method comprising checking, using a control unit, whether time (t) greater than or equal to a predetermined time period lapsed after the ignition of an engine of the automobile, if yes, initiating sampling of an output voltage using a sensor based system having one or more pressure sensors disposed inside the fuel tank, checking an output voltage (V) of at least one pressure sensor of the sensor based system, wherein the control unit checks whether the sensor output voltage (V) is less than a predetermined value, and initializing an odometer reading counter (c).